The last decade: the New Zealand architectural designs of Friedensreich Hundertwasser (1928-2000) in the 1990s - Tyler, Linda (Architectural History Aotearoa, 2020)
Constructivist in his approach to both painting and architecture, the Austrian designer Friedensreich Hundertwasser’s technical innovations in building anticipated many of the principles of sustainability which characterize eco-structures. These include rooftop planting for insulation and temperature control, rainwater harvesting and use of recycled materials including glassware. His regeneration of Kaurinui in Northland has been located by some within the tradition of Land Art in the way in which it interconnects ecology and humanity. He became a New Zealand citizen in 1986 and produced an architectural model called "Spiral Monument" as his entry for the architectural competition for the Museum of New Zealand in 1990. In it, some have seen a hybridizing of Robert Smithson’s Spiral Jetty with Māori spiral designs. In 2021, his 1993 plan for improving a council building in the Town Basin in Whangārei and making it into an art gallery will come to fruition. His 1998 Kawakawa toilets have become iconic in the North. This paper will consider how these designs from the 1990s reflect Hundertwasser ongoing concern with rejecting rationalism in architecture.